Eficiencia agronómica de cinco programas de fertilización combinados con materia orgánica, sobre el rendimiento del cultivo de maíz, en la zona de Milagro - Martínez Meza, Karla Geovanna (2020)
This research work was carried out in the “La Mina” farm land owned by Ms. Karla Martínez located at km 3.5 of the Milagro-Virgen de Fatima road, in the province of Guayas. As a planting material, the AVG-9363 corn hybrid was used. The treatments were made up of twelve treatments with 3 repetitions that gives a total of 36 plots. The first six treatments were applied with Humus 1500 kg / ha with different levels of balanced fertilization with N-P-K-S-Zn-B and the remaining six with Compost 300 kg / ha with the same fertilization levels. The statistical design used was divided plots in factorial arrangement, calculating the analysis of variance and comparisons of treatments with the 95% Tukey test. For the establishment of the crop, the relevant cultural work was carried out. The results show that the application of Humus together a fertilization program 130-40-80-30-2,0-1,5 kg / ha (N-P-K-S-Zn-B), increases the yield of grain per hectare. In addition, it generates higher income. However, it is shown that it shows that the fertilization program 110-30-70-20-1.5-1.0 kg / ha (N-P-K-S-Zn-B) had the best nutrient assimilation rate.